The dawn of Western sinology: the contribution of Fernández de Navarrete - Busquets, Anna (2016)
During the sixteenth and seventeenth centuries, the publications about China written by the Jesuits enjoyed of a great popularity and reputation in Europe. In this context, the publications from mendicant orders remained, in many cases, relegated to a second sphere. Such is the case of the Tratados historicos, politicos, eticos y religiosos de la monarchia de China,published that the Dominican Domingo Fernández de Navarrete published in 1676. The aim of this article is to highlit the figure of this missionary and value this publication in terms of its contribution to the knowledge of China .